Implementasi Sistem Konfigurasi Dasar Mikrotik Berbasis Desktop Wizard dengan Antarmuka Grafis untuk Setup Jaringan: Rekayasa Keamanan Siber - dpurwanto; Yudhi Darmawan; Transisma Budiarta (Jurnal Telkommil, 2026)
The configuration of MikroTik RouterOS devices through Winbox is still done manually with a modular-technical interface, which is time-consuming, error-prone, and difficult for non-technical users. This study aims to design and implement a desktop wizard application with a graphical user interface (GUI) for basic MikroTik configuration, utilize the RouterOS API for snapshot-based automation, and compare the ease of use and efficiency between the wizard system and manual Winbox configuration. The application was developed using Python with CustomTkinter as the GUI framework and communicates with MikroTik devices via RouterOS API on TCP port 8728. The system development follows the Waterfall method, covering requirements analysis, system design, implementation, and testing phases. Testing was conducted using Black Box Testing for functionality verification and System Usability Scale (SUS) for usability measurement, along with configuration time comparison between the wizard system and manual Winbox. Black Box Testing results show that all 8 configuration modules function correctly with a 100% success rate. The SUS evaluation yielded an average score of 78.5, categorized as “Acceptable (Good).” Time comparison testing demonstrates that the wizard system reduces configuration time by an average of 58.3% compared to manual Winbox configuration. This research concludes that the desktop wizard application effectively simplifies MikroTik configuration, provides snapshot-based rollback capability, and significantly improves both ease of use and efficiency for network administrators.